International evidence on ethical mutual fund performance and investment style - Bauer, Rob; Koedijk, Kees; Otten, Rogér (Journal of Banking & Finance, 2005)
Using an international database containing 103 German, UK and US ethical mutual funds we review and extend previous research on ethical mutual fund performance. By applying a Carhart multi-factor model [Carhart, Journal of Finance 57 (1997) 57] we overcome the benchmark problem most prior ethical studies suffered from. After controlling for investment style, we find no evidence of significant differences in risk-adjusted returns between ethical and conventional funds for the 1990–2001 period. Our results also suggest that ethical mutual funds underwent a catching up phase, before delivering financial returns similar to those of conventional mutual funds. Finally, our performance estimates are robust to the inclusion of ethical indexes, which, surprisingly, are not incrementally capable of explaining ethical mutual fund return variation.